Secrecy analysis for orthogonal time frequency space technique based LEO satellite communication - Zan LI; Junfan HU; Bing LI; Jia SHI; Jiangbo SI (Tongxin xuebao)
In order to improve the security performance of low earth orbit (LEO) satellite downlink communication system, a cooperative UAV was employed to send jamming signals against the eavesdroppers.In particular, the downlink transmission was based on the orthogonal time frequency space (OTFS) technique to combat the severe Doppler effect caused by the high mobility of the LEO satellite.The closed form expression for the security outage probability (SOP) was derived at the legitimate receiver, where a novel moment matching approach was used for finding a summed probability distribution function (PDF) of the shadowed-Rician (SR) distributed terms.Simulation results prove that the SOP performance advantage of the downlink LEO satellite communication achieved by OTFS over OFDM scheme, and show the effectiveness of employing unmanned aerial vehicle (UAV) jammer in terms of enhancing secrecy transmission.